2014
DOI: 10.4103/0019-5154.135486
|View full text |Cite
|
Sign up to set email alerts
|

T-cell rich angiomatoid polypoid pseudolymphoma: A novel cutaneous pseudolymphoma

Abstract: Cutaneous pseudolymphomas refer to a group of benign reactive T or B cell lymphoproliferative processes that simulate cutaneous lymphomas. T cell rich angiomatoid polypoid pseudo lymphoma (TRAPP) of the skin is a unique form of T cell rich cutaneous pseudolymphoma. A 13-year-girl presented with an asymptomatic skin colored papule on the right elbow, the biopsy of which revealed features consistent with TRAPP. The dermis showed an infiltrate of lymphocytes, plasma cells, and histiocytes along with prominent vas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 4 publications
(7 reference statements)
0
3
0
1
Order By: Relevance
“…TRAPP is defined by its name as a cutaneous lymphoid proliferation that resembles a vascular tumor clinically and mimics a lymphoma histologically [1]. Only a few studies of TRAPP have been published in the literature so far [1,2]. Dayrit et al identified TRAPP in 2011 and described it in detail in their clinicopathological study of 17 patients [1].…”
Section: Discussionmentioning
confidence: 99%
“…TRAPP is defined by its name as a cutaneous lymphoid proliferation that resembles a vascular tumor clinically and mimics a lymphoma histologically [1]. Only a few studies of TRAPP have been published in the literature so far [1,2]. Dayrit et al identified TRAPP in 2011 and described it in detail in their clinicopathological study of 17 patients [1].…”
Section: Discussionmentioning
confidence: 99%
“…Das T-Zell-reiche angiomatöse polypoide Pseudolymphom ist, wie der Name bereits sagt, eine kutane lymphoide Proliferation, die klinisch an einen vaskulären Tumor und histologisch an ein Lymphom erinnert [1]. Bisher gibt es in der Literatur nur wenige Veröffentlichungen zu dieser Entität [1,2]. Dayrit [7].…”
Section: Diskussionunclassified
“…Cutaneous pseudolymphomas are a group of benign reactive T-cell or B-cell lymphoproliferative processes of varying etiologies that can mimic lymphoma. [ 1 2 ] One of the precipitating factors for pseudolymphoma is drugs like anticonvulsants, antidepressants, angiotensin-converting enzyme inhibitors and antihistamines. [ 2 ] We report an 80-year-old male patient on phenytoin who presented with skin lesions resembling cutaneous lymphoma which showed complete resolution on withdrawal of the drug.…”
Section: Introductionmentioning
confidence: 99%